2014
DOI: 10.1111/his.12383
|View full text |Cite
|
Sign up to set email alerts
|

Napsin A is a useful marker for metastatic adenocarcinomas of pulmonary origin

Abstract: These data suggest that napsin A may be a useful marker for identifying metastatic adenocarcinomas of pulmonary origin in combination with TTF-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Our findings in ovarian nonmucinous carcinomas are consistent with previous studies, in which napsin A overexpression has been observed almost exclusively in O-CCC [10][11][12][13] but only in up to 10% of O-EC and less than 1% of HGSC cases [10][11][12]. The distinction between O-CCC and HGSC is important because they differ in chemotherapeutic response, risk of thromboembolic complications, pattern of recurrence, prognosis, and association with specific genetic syndromes (ie, the association of O-CCC in young patients with Lynch syndrome and of HGSC with germline BRCA1 and/or BRCA2 mutations).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings in ovarian nonmucinous carcinomas are consistent with previous studies, in which napsin A overexpression has been observed almost exclusively in O-CCC [10][11][12][13] but only in up to 10% of O-EC and less than 1% of HGSC cases [10][11][12]. The distinction between O-CCC and HGSC is important because they differ in chemotherapeutic response, risk of thromboembolic complications, pattern of recurrence, prognosis, and association with specific genetic syndromes (ie, the association of O-CCC in young patients with Lynch syndrome and of HGSC with germline BRCA1 and/or BRCA2 mutations).…”
Section: Discussionsupporting
confidence: 93%
“…The present data demonstrate that napsin A is an additional marker that is useful for O-CCC diagnosis. Our findings of napsin A expression in 66.7% of EM-CCCs and 4.5% of EM-ECs are also consistent with previous reports revealing its expression in 67% to 93% of EM-CCC and in less than 10% of EM-EC [9,11,[14][15][16][17]. Most EM carcinomas are of the low-grade endometrioid type (grade 1 and grade 2), confined to the uterus, and are associated with a favorable prognosis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations